2012
DOI: 10.1371/journal.pone.0035554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-Lethal Exposure to Ultraviolet Radiation on the Escape Performance of Atlantic Cod Larvae (Gadus morhua)

Abstract: The amount of ultraviolet (UV) radiation reaching the earth's surface has increased due to depletion of the ozone layer. Several studies have reported that UV radiation reduces survival of fish larvae. However, indirect and sub-lethal impacts of UV radiation on fish behavior have been given little consideration. We observed the escape performance of larval cod (24 dph, SL: 7.6±0.2 mm; 29 dph, SL: 8.2±0.3 mm) that had been exposed to sub-lethal levels of UV radiation vs. unexposed controls. Two predators were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…High variability on UVB tolerance during larval stages have been shown among fish species (Fukunishi et al 2012;Mitchell et al 2008;Sucré et al 2012;Vehniäinen et al 2012). Caspian Sea salmon (Salmo trutta caspius) larvae exposed to 0.5-1.3 W m -2 experienced 100% mortality after 9 days of exposure to UVR (Kazerouni and Khodabandeh 2011).…”
Section: Detrimental Effects Of Uvr On Fishmentioning
confidence: 99%
“…High variability on UVB tolerance during larval stages have been shown among fish species (Fukunishi et al 2012;Mitchell et al 2008;Sucré et al 2012;Vehniäinen et al 2012). Caspian Sea salmon (Salmo trutta caspius) larvae exposed to 0.5-1.3 W m -2 experienced 100% mortality after 9 days of exposure to UVR (Kazerouni and Khodabandeh 2011).…”
Section: Detrimental Effects Of Uvr On Fishmentioning
confidence: 99%
“…This protein has a strong activity during embryogenesis, and it, too, has been linked to the formation of skin tumors in response to UV radiation [36,37]. Ultraviolet radiation also decreases the capacity of fish to escape from predators, as demonstrated for cod larvae by Fukunishi et al [38].…”
Section: Rerio Single Exposuresmentioning
confidence: 97%
“…Other direct effects of UV exposure on fish eggs or larvae include malformation (Dong et al, 2007), retarded growth (Jokinen et al, 2008), lesion of skin, eyes, and brain (Blazer et al, 1997;McFadzen et al, 2000), and weakened immune system (Markkula et al, 2005, 2006). These pernicious effects may be higher for fish larvae that are often present in surface waters since UV-B (λ = 280-320 nm) exposure induces DNA damage in a variety of fish larvae such as Atlantic cod, northern anchovy Englausis mordax, icefish Cephalus aceratus and Japanese medaka Oryzias latipes (see Fukunishi et al, 2012 for references). UV-B exposure is also likely to weaken fish larvae by inducing physiological stress and damage as suggested by a study that observed a decrease in cod larval escape response to predators, which can increase the impact of predation on fish recruitment success (Fukunishi et al, 2012).…”
Section: Importance Of Light Radiation For Carotenoid Production and mentioning
confidence: 99%
“…These pernicious effects may be higher for fish larvae that are often present in surface waters since UV-B (λ = 280-320 nm) exposure induces DNA damage in a variety of fish larvae such as Atlantic cod, northern anchovy Englausis mordax, icefish Cephalus aceratus and Japanese medaka Oryzias latipes (see Fukunishi et al, 2012 for references). UV-B exposure is also likely to weaken fish larvae by inducing physiological stress and damage as suggested by a study that observed a decrease in cod larval escape response to predators, which can increase the impact of predation on fish recruitment success (Fukunishi et al, 2012). The extent of UV induced damage is largely modulated by the presence of competent photoprotection by e.g., carotenoids, mycosporine-like amino acids (MAAs) and other pigments, and photorepair systems.…”
Section: Importance Of Light Radiation For Carotenoid Production and mentioning
confidence: 99%